Cat's whiskers Cleome gynandra L. - Chweya, J.A.; Mnzava, N.A.; Leibniz Institute of Plant Genetics and Crop Plant Research (1997)
Cat's whiskers (Cleome gynandra) grows as a weed in most tropical countries, but is a semi-cultivated, popular tropical leafy vegetable in many parts of sub-Saharan Africa especially in most countries in eastern and southern Africa. This book presents information on its genetic resources in a series of chapters on the following topics: taxonomy, botany, origin and centre of diversity, properties and uses, characterization, evaluation and conservation, breeding, production, ecology, agronomy, and limitations, prospects and research needs. An appendix details researchers and institutions working on indigenous leafy vegetables in sub-Saharan Africa. (Abstract © CAB ABSTRACTS, CAB International)